Dependence of fatigue limit on stress ratio and influence of cyclic stress on shear strength for an adhesive lap joint. Issue 12 (10th September 2021) - Houjou, K.; Shimamoto, K.; Akiyama, H.; Sato, C.
ABSTRACT: The improvement in adhesion technology for joining different types of materials has led to expectations of weight reduction in cars and commercial vehicles. Various levels of stress and stress ratios are loaded onto the joints of such transport vehicles. Therefore, the fatigue shear strength of an adhesive lap joint is important. This study is related to the fatigue properties of structural adhesive joints. Lap-joint specimens using epoxy adhesive were prepared, and fatigue tests with four different stress ratios were conducted. Subsequently, the fatigue limit diagram was plotted, and the effect of stress ratio on the fatigue limit was investigated. Moreover, the strength of the specimens subjected to various cyclic stress levels was investigated systemically. With cyclic shear stress, the influence of the shear stress amplitude on the resistance to fatigue failure was more significant than that of the number of cycles. The specimens that endured the fatigue tests maintained approximately the same shear strength as that of the as-received specimens. The findings of this study can provide important guidance for the design of a car body.